2019
DOI: 10.9734/ajacr/2019/v3i430095
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Characterization of Oil from Date Palm (Phoenix dactylifera) Seed

Abstract: This work focuses on the extraction of oil from date palm seed. Using n-hexane in Soxlet extraction apparatus, standard procedures were followed to determine the oil feed stock yield. Proximate compositions and physicochemical characteristics were carried out. Also, Fourier Transform Infrared Spectroscopy (FTIR) and Gas Chromatography Mass Spectrometry (GC-MS) were used to determine the functional groups and the fatty acid composition of the oil respectively. The result shows that the appearance of date palm s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…The peak at 721 cm –1 corresponds to the aromatic compounds. These results were similar to those obtained in the literature. The FTIR spectra of Eudragit RS100 showed characteristic peaks at 2950 cm –1 due to CH aliphatic stretching, at 1722 cm –1 due to CO ester stretching, and a peak at 1143 cm –1 that corresponds to the CO ester group. This was in accordance with what was reported. , Matching up to the FTIR spectrum of Eudragit with the oil-loaded nanoparticles revealed a reduction in the intensity of the peak at 1725 cm –1 as well as coming out of three jointed peaks in 2924, 2853, and 1466 cm –1 that characterize DS oil.…”
Section: Resultssupporting
confidence: 90%
“…The peak at 721 cm –1 corresponds to the aromatic compounds. These results were similar to those obtained in the literature. The FTIR spectra of Eudragit RS100 showed characteristic peaks at 2950 cm –1 due to CH aliphatic stretching, at 1722 cm –1 due to CO ester stretching, and a peak at 1143 cm –1 that corresponds to the CO ester group. This was in accordance with what was reported. , Matching up to the FTIR spectrum of Eudragit with the oil-loaded nanoparticles revealed a reduction in the intensity of the peak at 1725 cm –1 as well as coming out of three jointed peaks in 2924, 2853, and 1466 cm –1 that characterize DS oil.…”
Section: Resultssupporting
confidence: 90%
“…The peaks at 1743 and 1160 cm -1 correspond to stretching vibration of the C=O and C-O groups of the ester, respectively. These findings were in agreement with those reported in [48][49][50][51][52].…”
Section: Fourier Transform Infrared Spectroscopy Analysissupporting
confidence: 94%
“…Besides, date seeds are used as animal feed or caffeine-free coffee replacements in some areas. The Ajwa date seed oil includes sterol, phytochemistry, oleic, palmitic and fatty acids and their derivatives; these have antibacterial, antioxidant, anticancer and antilipidemic effects [72,73]. The present work reported that Ajwa date seed oil (AWSO) contains hexadecanamide, 5-hydroxymethylfurfura, 9-octadecenamide, (Z)-, oleic acid, cis-11-eicosenamide, dodecanoic acid and palmitic acid.…”
Section: Discussionmentioning
confidence: 85%